Evaluation of Awards and Recognition Programs in Increasing Employee Motivation in Companies - Gina Pratiwi Suciyono; Debby Putri Wahyu Aji; Editya Nurdiana (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
Rewards and recognition programs are an important element in a human resource (HR) management strategy that aims to improve employee motivation and performance. This study aims to analyze the effectiveness of reward and recognition programs in increasing employee motivation in rattan companies, identify factors that affect their success, and provide practical recommendations for companies. The research method used is a quantitative approach with a survey using a structured questionnaire, complemented by a qualitative approach through interviews and focused group discussions. Data analysis involves descriptive and inferential statistical techniques. The results showed that financial and skill development-based rewards had the greatest influence on employee motivation, with a regression coefficient value of 0.65 (p<0.05). The relevance factor of awards to employee needs was also proven to be significant, with a coefficient of 0.45 (p<0.05). Interviews and group discussions revealed the importance of transparency and fairness in the implementation of reward programs to prevent negative impacts on motivation. The study concludes that the effectiveness of the award program is highly dependent on the relevance of the program design to the needs of employees as well as their involvement in the design process. Practical recommendations include the development of transparent, flexible, and contextual reward policies to improve employee motivation and performance in a competitive rattan industry. This research is expected to make a significant contribution to improving human resource management in this sector.